MAP4-dependent regulation of microtubule formation affects centrosome, cilia, and golgi architecture as a central mechanism in growth regulation - Zahnleiter, Diana; Hauer, Nadine; Keßler, Kristin; Uebe, Steffen; Sugano, Yuya; Neuhauss, Stephan C. F.; Gießl, Andreas; Ekici, Arif Bülent; Blessing, Holger; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Human Mutation, 2015)
Numerous genes are involved in human growth regulation. Recently, autosomal-recessive inherited variants in centrosomal proteins have been identified in Seckel syndrome, primary microcephaly, or microcephalic osteodysplastic primary dwarfism. Common hallmarks of these syndromic forms are severe short stature and microcephaly. In a consanguineous family with two affected children with severe growth retardation and normocephaly, we used homozygosity mapping and next-generation sequencing to identify a homozygous MAP4 variant. MAP4 is a major protein for microtubule assembly during mitosis. High-expression levels in the somite boundaries of zebrafish suggested a role in growth and body segment patterning. The identified variant affects binding sites of kinases necessary for dynamic instability of microtubule formation. We found centrosome amplifications in mitotic fibroblast cells in vivo and in vitro. These numeric centrosomal aberrations were also present during interphase resulting in aberrant ciliogenesis. Furthermore, affected cells showed a dysfunction of the microtubule-dependent assembly of the Golgi apparatus, indicated by a significant lack of compactness of Golgi membranes. These observations demonstrated that MAP4 mutations contribute to the clinical spectrum of centrosomal defects and confirmed the complex role of a centrosomal protein in centrosomal, ciliary, and Golgi regulation associated with severe short stature.
EVALuna2:9244